Autonomy in Indonesian Counseling Students at Universities: A Comparative Study - Yuca, Verlanda; Suherman, Uman; Nurihsan, Juntika; Budiman, Nandang; Magistarina, Elrisfa (Universitas Negeri Padang, 2025)
Student autonomy refers to an individual's ability to manage their own learning process, make informed academic decisions, and take responsibility for their personal development. The level of autonomy can vary depending on the campus environment, learning approach, and the type of academic support provided. This study aims to describe and analyze the differences in student autonomy between Universitas Negeri Padang (UNP) and Universitas Pendidikan Indonesia (UPI). This study used a comparative, descriptive, and quantitative approach. Samples were purposively selected from students at Universitas Negeri Padang and Universitas Pendidikan Indonesia who actively attended lectures. The data collection instrument was The Autonomy Questionnaire for Students with the Guttman scale model with